Variations on the Canon : Essays on Music from Bach to Boulez in Honor of Charles Rosen on His Eightieth Birthday /: Essays on Music from Bach to Boulez in Honor of Charles Rosen on His Eightieth Birthday. (2008) - Unknown
No abstract available